COMMUNITY study - Thålin, Charlotte; Havervall, Sebastian; Marking, Ulrika; Greilert-Norin, Nina; Blom, Kim; Gordon, Max; Klingström, Jonas; Nilsson, Peter; Hober, Sophia; Phillipson, Mia; Mangsbo, Sara; Åberg, Mikael (Karolinska Institutet, 2022)
The COMMUNITY pandemic surveillance cohort is a longitudinal cohort study including 2149 healthcare workers and 118 COVID-19 patients.

Dataset includes:

1. Serological data at baseline April-May 2020 and at follow-up every four month (ongoing).

2. Data on memory T cell responses

3. Register data from Swedish vaccination register (VAL Vaccinera) and national communicable diseases register SmiNet (Public Health Agency of Sweden).

3. Self-reported symptoms compatible with COVID-19 since 1 January 2020, occupation, work location and exposure to patients infected with SARS-CoV-2 prior to blood sampling (healthcare workers).

3. Clinical data including co-morbidities, disease severity, on-going medications, demography (COVID-19 patients).

Abstract

The COMMUNITY pandemic surveillance cohort was initiated in April 2020 and comprises 2149 healthcare workers and 118 COVID-19 patients. Blood samples are collected every four months. Serological and cellular immune responses are continuously mapped to demography, vaccination(s) and prior infection. qPCR screening programs, including viral sequencing and culturing, are conducted during time points with high viral transmission and in response to the threat of emerging variants of concern (VOC).

The COMMUNITY pandemic surveillance cohort is conducted through close collaborations within the SciLifeLab community, the Public Health Agency of Sweden and the Swedish Armed Forces.

Publications

Impact of SARS-CoV-2 infection on vaccine-induced immune responses over time. (http://www.ncbi.nlm.nih.gov/pubmed/35444806) Havervall S, Marking U, Greilert-Norin N et al. Clinical & Translational Immunology 2022;11(4):e1388. https://doi.org/10.1002/cti2.1388

Duration of SARS-CoV-2 Immune Responses Up to Six Months Following Homologous or Heterologous Primary Immunization with ChAdOx1 nCoV-19 and BNT162b2 mRNA Vaccines. (http://www.ncbi.nlm.nih.gov/pubmed/35334989) Marking U, Havervall S, Greilert-Norin N, et al.  Vaccines 2022;10(3). https://doi.org/10.3390/vaccines10030359

A cell-free high throughput assay for assessment of SARS-CoV-2 neutralizing antibodies. (http://www.ncbi.nlm.nih.gov/pubmed/34628049) Mravinacova S, Jönsson M, Christ W, Klingström J . et al.

New biotechnology 2022;66():46-52. https://doi.org/10.1016/j.nbt.2021.10.002

Long-term SARS-CoV-2-specific and cross-reactive cellular immune responses correlate with humoral responses, disease severity, and symptomatology. (http://www.ncbi.nlm.nih.gov/pubmed/35349756) Laurén I, Havervall S, Ng H, Lord M, Pettke A, Greilert-Norin et al. Immunity, inflammation and disease 2022;10(4):e595. https://doi.org/10.1002/iid3.595

Persistent endotheliopathy in the pathogenesis of long COVID syndrome: Comment from von Meijenfeldt et al. (http://www.ncbi.nlm.nih.gov/pubmed/34731533) Von Meijenfeldt Fa, Havervall S, Adelmeijer J, Thalin C, Lisman T JOURNAL OF THROMBOSIS AND HAEMOSTASIS 2022;20(1):267-269. https://doi.org/10.1111/jth.15580

Robust humoral and cellular immune responses and low risk for reinfection at least 8 months following asymptomatic to mild COVID-19. (http://www.ncbi.nlm.nih.gov/pubmed/34459525) Havervall S, Ng H, Falk Aj, Greilert-Norin et al. JOURNAL OF INTERNAL MEDICINE 2022;291(1):72-80. https://doi.org/10.1111/joim.13387

SARS-CoV-2 induces a durable and antigen specific humoral immunity after asymptomatic to mild COVID-19 infection (http://www.ncbi.nlm.nih.gov/pubmed/35020778) . Havervall S, Jernbom Falk A, Klingström J et al.. PloS one 2022;17(1):e0262169. https://doi.org/10.1371/journal.pone.0262169

A Model Predicting Mortality of Hospitalized Covid-19 Patients Four Days After Admission: Development, Internal and Temporal-External Validation (http://www.ncbi.nlm.nih.gov/pubmed/35141170) . Heber S, Pereyra D, Schrottmaier Wc et al.Assinger A Frontiers in cellular and infection microbiology 2021;11():795026. https://doi.org/10.3389/fcimb.2021.795026

An evaluation of a FluoroSpot assay as a diagnostic tool to determine SARS-CoV-2 specific T cell responses. Mangsbo Sm, Havervall S, Laurén I et al. PloS one. 2021;16(9):e0258041. https/doi.org/10.1371/journal.pone.0258041 (https://doi.org/10.1371/journal.pone.0258041)

Antibody responses after a single dose of ChAdOx1 nCoV-19 vaccine in healthcare workers previously infected with SARS-CoV-2 (http://www.ncbi.nlm.nih.gov/pubmed/34391088) . Havervall S, Marking U, Greilert-Norin N, Ng H, Gordon M, Salomonsson Ac, Hellström C, Pin E, Blom K, Mangsbo S, Phillipson M, Klingström J, Hober S, Nilsson P, Åberg M, Thålin C. EBioMedicine 2021;70():103523. htttps//doi.org/10.1016/j.ebiom.2021.103523 (https://doi.org/10.1016/j.ebiom.2021.103523)

Circulating Markers of Neutrophil Extracellular Traps Are of Prognostic Value in Patients With COVID-19. (http://www.ncbi.nlm.nih.gov/pubmed/33267662) Ng H, Havervall S, Rosell A, Aguilera K, Parv K, Von Meijenfeldt Fa, Lisman T, Mackman N, Thålin C, Phillipson M. Arteriosclerosis, Thrombosis, and Vascular Biology 2021;41(2):988-994. https/doi.org/10.1161/ATVBAHA.120.315267 (https://doi.org/10.1161/atvbaha.120.315267)

COVID-19 is Associated with an Acquired Factor XIII Deficiency. (http://www.ncbi.nlm.nih.gov/pubmed/33742434) Von Meijenfeldt Fa, Havervall S, Adelmeijer J, Lundström A, Magnusson M, Mackman N, Thalin C, Lisman T. Thrombosis and Haemostasis 2021;121(12):1668-1669. https://doi.org/ 10.1055/a-1450-8414 (https://doi.org/10.1055/a-1450-8414)

Elevated factor V activity and antigen levels in patients with Covid-19 are related to disease severity and 30-day mortality. (http://www.ncbi.nlm.nih.gov/pubmed/33393103) Von Meijenfeldt Fa, Havervall S, Adelmeijer J, Lundström A, et al. American Journal of Hematology 2021;96(4):E98-E100. https://doi.org/10.1002/ajh.26085

Patients With COVID-19 Have Elevated Levels of Circulating Extracellular Vesicle Tissue Factor Activity That Is Associated With Severity and Mortality-Brief Report (http://www.ncbi.nlm.nih.gov/pubmed/33267656)

Rosell A, Havervall S, Von Meijenfeldt F, et al.

Arteriosclerosis, thrombosis, and vascular biology 2021;41(2):878-882 . https://doi.org/10.1002/rth2.12462

Prothrombotic changes in patients with COVID-19 are associated with disease severity and mortality (http://www.ncbi.nlm.nih.gov/pubmed/33537537)

Von Meijenfeldt Fa, Havervall S, Adelmeijer J et al. Research and practice in thrombosis and haemostasis 2021;5(1):132-141

Soluble angiotensin-converting enzyme 2 is transiently elevated in COVID-19 and correlates with specific inflammatory and endothelial markers (http://www.ncbi.nlm.nih.gov/pubmed/34138483)

Lundström A, Ziegler L, Havervall S. et al.

Journal of Medical Virology 2021;93(10):5908-5916

Sustained prothrombotic changes in COVID-19 patients 4 months after hospital discharge. (http://www.ncbi.nlm.nih.gov/pubmed/33560386) Von Meijenfeldt Fa, Havervall S, Adelmeijer J, et al.  Blood Advances 2021;5(3):756-759. https://doi.org/10.1182/bloodadvances.2020003968

Symptoms and Functional Impairment Assessed 8 Months After Mild COVID-19 Among Health Care Workers (http://www.ncbi.nlm.nih.gov/pubmed/33825846)

Havervall et al. JAMA 2021;325(19):2015-2016. https://doi.org/10.1001/jama.2021.5612

Systematic evaluation of SARS-CoV-2 antigens enables a highly specific and sensitive multiplex serological COVID-19 assay. (http://www.ncbi.nlm.nih.gov/pubmed/34295471) Hober S, Hellstrom C, Olofsson J et al. CLINICAL & TRANSLATIONAL IMMUNOLOGY 2021;10(7):e1312.

https://doi.org/10.1002/cti2.1312

SARS-CoV-2 exposure, symptoms and seroprevalence in healthcare workers in Sweden. (http://www.ncbi.nlm.nih.gov/pubmed/33033249) Rudberg As, Havervall S, Månberg A, Jernbom Falk A, et al. C. Nature Communications 2020;11(1):5064 https:/doi.org/10.1038/s41467-020-18848-0 (https://doi.org/10.1038/s41467-020-18848-0)
Keywords: Cellular immunology; Clinical sciences not elsewhere classified; Occupational and workplace health and safety; Epidemiology not elsewhere classified; Health care administration; Humoural immunology and immunochemistry; Medical and Health Sciences; Medicin och hälsovetenskap; Immunology; Immunologi; Epidemiology; Epidemiologi